2015
DOI: 10.5539/jel.v4n3p25
|View full text |Cite
|
Sign up to set email alerts
|

Path Analysis on the Factors Influencing Learning Outcome for Hospitality Interns–From the Flow Theory Perspective

Abstract: Learning outcome is an important indicator for educators in evaluating curriculum design. The focus of this study has been to examine the factors within internship programs, recognizing the complex nature of knowledge application in a practical industry environment. Flow theory was adopted to explain the psychological state of hospitality students during internship and relate it to their learning outcome. A total of 152 responses were collected via self-administrated questionnaires from hospitality students at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…There are studies in the internship literature that provide insight into career plan changes after the internship experience. After carrying out internships in the tourism sector (Farmaki, 2018;Kim & Park, 2013;Köşker & Unur, 2017;Wang & Chen, 2015) and in the health sector (Öztürk & Kıraç, 2019), the thought of a career in the jobs and sectors of the internships was found to be negatively affected. Robinson et al (2016) indicated that the tendency to change career plans because of internship experience in the tourism and hospitality sector involves changes within the sector rather than cross-sectoral changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies in the internship literature that provide insight into career plan changes after the internship experience. After carrying out internships in the tourism sector (Farmaki, 2018;Kim & Park, 2013;Köşker & Unur, 2017;Wang & Chen, 2015) and in the health sector (Öztürk & Kıraç, 2019), the thought of a career in the jobs and sectors of the internships was found to be negatively affected. Robinson et al (2016) indicated that the tendency to change career plans because of internship experience in the tourism and hospitality sector involves changes within the sector rather than cross-sectoral changes.…”
Section: Discussionmentioning
confidence: 99%
“…Internship programs help students understand the contexts of business and which job fields may be suitable for them in their future professional life (Goia (Agoston) et Rothman & Sisman, 2016;Wang & Chen, 2015). Likewise, Kim and Park (2013) argued that students' first impressions during their internships are essential for their career orientation.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Internships are work-based learning opportunities, either taking place as part of formal education (with interns having a student status) or outside of formal education (also after graduation), during which a person spends a period of time in an organization to acquire specific competencies required by the labor market [9]. Internships are aimed to facilitate students' learning processes from practitioners [10] and to improve their learning outcomes. The most important feature of internships is that they give students the opportunity to see through personal learning experience what working in a certain company environment really entails [3].…”
Section: The Role Of Internships In Experiential Learningmentioning
confidence: 99%
“…In medical, education, and hospitality industries, students' motivation to take part in internships depends on the learning outcomes measured by their expected acquisition of credible experience trough practical activities [10]; in the respective industries, students valuate the most the capacity of an internship program to make their educational experience more relevant and useful to future careers. In the USA hospitality industry, research focusing on three variables-work content, supervision, and appraisals during internships-indicated that the job content was considered a motivator, triggering interns' responsibility and satisfaction [40].…”
Section: Factors Influencing the Quality Of Internshipsmentioning
confidence: 99%
“…There are several reports on the advantages of internship programs that make students understand the importance of person-job fit and person-organisation fit (Dessler, 2013). Internship learning represents an essential tool for completing their formal education and conditioning their further career path (Wang and Chen, 2015). There is evidence that interns are better prepared to enter the job market than non-interns (Gault et al, 2000;Hite and Bellizzi, 1986).…”
Section: Introductionmentioning
confidence: 99%